The Place of Corporate Social Responsibility and its Activities in the Retail Firm Management - Katarína Kleinová; Zuzana Lušňáková (Polityki Europejskie, Finanse i Marketing)
The paper deals with the important involvement of the retail firm - Corporate Social Responsibility (CSR) and its place and activities in the retail firm management. For the purpose of this paper we choose one of the Slovak retail firms. The main objective of the article is to find out, how CSR is placed in chosen firms activities. Besides other areas of CSR activities special emphasis is put on the firm – customer relationship which will be the most important CSR task for the future. Qualitative research method, in-depth interviews, is chosen in order to analyse the research aim of this paper. The paper deals with the important involvement of the retail firm - Corporate Social Responsibility (CSR) and its place and activities in the retail firm management. For the purpose of this paper we choose one of the Slovak retail firms. The main objective of the article is to find out, how CSR is placed in chosen firms activities. Besides other areas of CSR activities special emphasis is put on the firm – customer relationship which will be the most important CSR task for the future. Qualitative research method, in-depth interviews, is chosen in order to analyse the research aim of this paper.